2021
DOI: 10.1016/j.heliyon.2021.e08092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness of three distraction techniques to allay dental anxiety during inferior alveolar nerve block in children: A randomized controlled clinical trial

Abstract: Background: Among the numerous methods used to control anxiety, distraction is the most popular method for controlling behavior during dental procedures in children. The present study aimed to use a fidget spinner, kaleidoscope, and virtual reality as distraction techniques individually and observe the effects on the anxiety levels of children subjected to inferior alveolar nerve block (IANB). Methods: In this parallel-group randomized clinical trial, 102 children aged 6-9 years requiring IANB for various dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…Many of the interventions designed to address DFA in children, such as modeling or distraction techniques, have limited evidence to support their use [ 15 , 28 , 235 , 236 ]. Research findings examining distraction and modeling techniques are mixed, with some studies reporting a decrease in DFA, whereas others found either mixed results or no difference (e.g., [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]). Tell–show–do, one of the most popular techniques utilized by dentists, likewise has little evidence to support its efficacy; however, it is widely accepted by children and parents, and there are no contraindications for its use [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the interventions designed to address DFA in children, such as modeling or distraction techniques, have limited evidence to support their use [ 15 , 28 , 235 , 236 ]. Research findings examining distraction and modeling techniques are mixed, with some studies reporting a decrease in DFA, whereas others found either mixed results or no difference (e.g., [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]). Tell–show–do, one of the most popular techniques utilized by dentists, likewise has little evidence to support its efficacy; however, it is widely accepted by children and parents, and there are no contraindications for its use [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 3 studies published during or before the 1990s [ 57 , 58 , 59 ], 4 studies published in the 2000s [ 60 , 61 , 62 , 63 ], and the majority of the included studies were published in the 2010s ( n = 30) [ 31 , 35 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] and 2020s ( n = 29) [ 50 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The age of the participants ranged from 3 to 12 years old. The investigated NPBIs included Tell–Show–Do ( n = 2) [ 75 , 92 ], distraction ( n = 6) [ 50 , 75 , 81 , 92 , 109 , 110 ], video modelling ( n = 4) [ 77 , 80 , 87 , 88 ], virtual reality (n = 9) [ 72 , 74 , 82 , 85 , 93 , 100 , 102 , 109 , 110 ], and visual pedagogy ( n = 3) [ 69 , 78 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations